MicroRNA-935 Directly Targets FZD6 to Inhibit the Proliferation of Human Glioblastoma and Correlate to Glioma Malignancy and Prognosis - Zhang, Dainan; Ma, Shunchang; Zhang, Chuanbao; Li, Peiliang; Mao, Beibei; Guan, Xiudong; Zhou, Wenjianlong; Peng, Jiayi; Wang, Xi; Li, Shaomin; Jia, Wang (Frontiers in Oncology, 2021)
MicroRNAs (miRNA) are involved in human glioblastoma multiforme (GBM). MiR-935 has been reported to have both tumor-inhibiting and tumorigenesis effect, but its role in GBM remains unclear. Because of the high mortality and morbidity associated with this malignancy, a deeper understanding of the molecular crosstalk that occurs in GBM is needed to identify new potential targets for treatment. At present, the mechanism of GBM at the molecular level is not fully understood. By using bioinformatic analysis, we found miR-935 was significantly down-regulated in GBM and presented a poorer outcome. In the glioma cell line and nude mice model, miR-935 inhibited cell proliferation by modulating cell circle in vitro and in vivo. Then the target genes of miR-935 was analyzed by using online database and the direct binding was tested by luciferase analysis. FZD6 was found to be a direct target of miR-935. The effect of miR-935 was recovered by FZD6 overexpression in vitro. In addition, the negative correlation of miR-935 and FZD6 expression was confirmed in our clinical samples, and the expression of FZD6 has a strong correlation with tumor malignancy and prognosis. This study showed that miR-935 directly inhibited FZD6 expression and inhibited the cell proliferation, thereby suppressing the development of GBM, suggesting that miR-935 is a cancer suppressor miRNA and may become a prognostic biomarker or a promising potential therapeutic target for human GBMs.